2017
DOI: 10.1101/186387
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clustering of adult-onset diabetes into novel subgroups guides therapy and improves prediction of outcome

Abstract: Research in context Evidence before this studyThe current diabetes classification into T1D and T2D relies primarily on presence (T1D) or absence (T2D) of autoantibodies against pancreatic islet beta cell autoantigens and age at diagnosis (earlier for T1D). With this approach 75-85% of patients are classified as T2D. A third subgroup, Latent Autoimmune Diabetes in Adults (LADA,<10%), is defined by presence of autoantibodies against glutamate decarboxylase (GADA) with onset in adult age. In addition, several rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(58 citation statements)
references
References 22 publications
1
57
0
Order By: Relevance
“…The responses to identical meals were assessed and high variability was shown between participants. Additionally, four sub‐types of type 2 diabetes have recently been identified, and Ahlqvist and colleagues have suggested that different sub‐types may respond differently to food, activity and medication, but acknowledged that further research is required to understand this fully. This is the first study to identify an individualised response to activity behaviour as suggested by Ahlqvist and colleagues …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The responses to identical meals were assessed and high variability was shown between participants. Additionally, four sub‐types of type 2 diabetes have recently been identified, and Ahlqvist and colleagues have suggested that different sub‐types may respond differently to food, activity and medication, but acknowledged that further research is required to understand this fully. This is the first study to identify an individualised response to activity behaviour as suggested by Ahlqvist and colleagues …”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence to support a more personalised approach to diabetes care and incorporating mobile technology could provide a mechanism for this tailored approach. A recent pilot study examined the use of personalised glucose feedback to change activity behaviour in non‐diabetic adults (n=33) and found that the feedback resulted in reduced sedentary time at follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…1 Tkaczynski (2017) implies that two-step clustering has been performed in many researches since its first version. It has been used in many applications from tourism to health, marketing to transportation (Ahlqvist et al, 2017;Kent, Jensen, & Kongsted, 2014;Cerin, Leslie, Du Toit, Owen, & Frank, 2007;Grifin et al, 2014;Hsu, Kang, & LAM, 2006). Beside its user friendly usage it has also many scientific advantages too.…”
Section: Outlier Detection With Two-step Clusteringmentioning
confidence: 99%
“…Despite the differences, these methods aim to produce subsets which have high intra-group similarities (objects within a group are similar), and low inter-group similarities (objects between groups are more dissimilar). Cluster analysis has widely been used to assess microarray data[35] and has seen success in EHR applications[11,3641]. Additionally, hierarchical clustering has been used to assess the contribution of obesity (a trait with known heterogeneity, as seen in Figure 1) to respiratory conditions[42,43].…”
Section: Machine Learning Approaches For Establishing a Phenotypementioning
confidence: 99%